Optimization of Biochar Application for Improving Soil Water Holding Capacity - Muhamad Fajar Sidiq; Reza Widyasaputra; Galang Indra Jaya; Mohammad Prasanto Bimantio; Amir Noviyanto; Moh Galih Purnama Jati; Bintang Wahyu Prasetyo; Arief Almuqhori Eka Nugraha (Jurnal Biologi Tropis, 2026)
Water scarcity limits soil productivity, but applying biochar can effectively enhance soil water retention in vulnerable areas. This study evaluated the effects of biochar types and application rates on the maximum moisture content of sandy soils in Gunungkidul, Indonesia. A completely randomized design was used to test rice husk and blotong biochar, alongside raw rice husk and a control, at varying application rates. Maximum soil moisture capacity was experimentally measured to determine treatment efficacy. Results indicated that biochar application significantly influenced soil moisture retention. Among the treatments, a lower application rate of rice husk biochar provided the most substantial improvement in water holding capacity compared to the control. Conversely, higher rates of biochar or the use of raw materials were less effective and, in some cases, reduced water retention. Conclusively, optimizing both the biochar feedstock and its application rate is critical; specific low-dose biochar applications can optimally enhance soil moisture retention, offering a practical strategy for sustainable agricultural management in semi-arid regions.